2018
DOI: 10.1073/pnas.1804674115
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic choriomeningitis virus Clone 13 infection causes either persistence or acute death dependent on IFN-1, cytotoxic T lymphocytes (CTLs), and host genetics

Abstract: Understanding of T cell exhaustion and successful therapy to restore T cell function was first described using Clone (Cl) 13 variant selected from the lymphocytic choriomeningitis virus (LCMV) Armstrong (ARM) 53b parental strain. T cell exhaustion plays a pivotal role in both persistent infections and cancers of mice and humans. C57BL/6, BALB, SWR/J, A/J, 129, C3H, and all but one collaborative cross (CC) mouse strain following Cl 13 infection have immunosuppressed T cell responses, high PD-1, and viral titers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 53 publications
3
43
0
Order By: Relevance
“…2E). Thus, the immunopathological features observed in LCMV Docile-infected B −/− mice were similar to those described for PD-1-deficient mice [5] or for particular mouse strains [6,7] after LCMV clone 13 infection.…”
Section: Prolonged Antigen Presentation and Vascular Leakage In B −/−supporting
confidence: 79%
“…2E). Thus, the immunopathological features observed in LCMV Docile-infected B −/− mice were similar to those described for PD-1-deficient mice [5] or for particular mouse strains [6,7] after LCMV clone 13 infection.…”
Section: Prolonged Antigen Presentation and Vascular Leakage In B −/−supporting
confidence: 79%
“…For instance, IFN is known to have both antiviral and immune suppressive effects. Our study has considered the former but not the latter, which is dominant late in infection, and which can be relieved by IFN blockade to achieve clearance of persistent infections (11)(12)(13). Finally, whereas in our minimal model CD8+ T cell exhaustion is fully reversible, recent studies have identified subsets of exhausted CD8+ T cells that cannot be reversed, especially with checkpoint inhibitors (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…The quest for an understanding of the outcomes of viral infections has led, over the years, to the identification of an array of factors, including the size of the viral inoculum (5), the innate and NK cell responses (6,30), and host genetic variations (13), that can potentially influence the outcomes. Here, we argue that underlying the effects of these factors is an essential dynamical motif, comprising the key interactions between antigens and CD8 T cells, that governs the outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations